Tourism as a Part of Sustainable Rural Development in the Area of Novi Pazar - Petrović, Dragan V.; Vukoičić, Danijela Ž.; Ristić, Dušan B. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
In insufficiently developed areas of Serbia, natural and anthropogenic tourist values are of great importance for sustainable rural development. In this study, a survey was conducted using the method of selecting respondents, where the analysis of economic, social, cultural, and environmental aspects took into consideration the current situation, with the goal of clearly defining all the strengths and weaknesses of rural settlements in Novi Pazar. The average values of related issues were used to calculate the value of the indicators, while the Sustainable Rural Development Index (SRDI) was determined by the average values of all indicators. The final outcome of the SRDI is 0.94, indicating that the area holds the potential to develop sustainable tourism. The results of the research can be used to plan the possibilities for further development of rural settlements in the researched area in order to minimize weaknesses and threats and maximize strengths and opportunities with the help of tourism based on sustainable development.